2016
DOI: 10.1037/apl0000048
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in justice evaluations: Evidence from fMRI.

Abstract: Justice research examining gender differences has yielded contrasting findings. This study enlists advanced techniques in cognitive neuroscience (fMRI) to examine gender differences in brain activation patterns in response to procedural and distributive justice manipulations. We integrate social role, information processing, justice, and neuroscience literature to posit and test for gender differences in 2 neural subsystems known to be involved in the appraisal of self-relevant events. Results indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 112 publications
6
55
2
Order By: Relevance
“…This finding is in line with evidence from laboratory experiments (Hack and Lammers, 2009;Dulebohn et al, 2016 for FMRI evidence) and from organizational surveys (e.g., Sweeney and McFarlin, 1997) that point towards women reacting more strongly to the fairness of procedures than men. However, other survey studies did not succeed in showing this difference (Fields et al, 2000;Lee et al, 2000;and Lee and Farh, 1999).…”
Section: Resultssupporting
confidence: 79%
“…This finding is in line with evidence from laboratory experiments (Hack and Lammers, 2009;Dulebohn et al, 2016 for FMRI evidence) and from organizational surveys (e.g., Sweeney and McFarlin, 1997) that point towards women reacting more strongly to the fairness of procedures than men. However, other survey studies did not succeed in showing this difference (Fields et al, 2000;Lee et al, 2000;and Lee and Farh, 1999).…”
Section: Resultssupporting
confidence: 79%
“…As is common for neuroimaging studies, general linear modelling (GLM) was used for the first-level analyses to identify an increase or decrease of the BOLD signal in response to the treatment versus the control treatment or baseline signal (Dimoka 2012;Dulebohn et al 2016). In most neuroscientific studies a GLM analysis is performed for each voxel 2 and for each participant (Dulebohn et al 2016). GLM analysis is appropriate when multiple predictors are used to indicate variability in a single, continuously distributed outcome variable.…”
Section: Mri Data Analysismentioning
confidence: 99%
“…With that said, we recognize three potential limitations. First, our sample was relatively limited in size, although being equivalent to, or larger than, other recent research in the organizational neuroscience realm (see Dulebohn et al., ; Vul, Harris, Winkielman, & Pashler, ). We suggest that our findings be replicated, doing so in a broad range of supervisory positions and organizational levels.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dulebohn et al. () used functional magnetic resonance imaging (fMRI) to investigate gender differences in how men and women process and respond neurologically to procedural and distributive justice stimuli. They found that the relationship between procedural justice information and activation in the salience subsystem of the brain (i.e., insula, anterior cingulate cortex, and ventral striatum) is stronger for women.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation